Revealing the mechanism of DNA passing through graphene and boron nitride nanopores. Issue 48 (4th December 2019) - Tyagi, Abhishek; Chu, Kelvin; Hossain, Md Delowar; Abidi, Irfan Haider; Lin, Weiyuan; Yan, Yuwei; Zhang, Kai; Luo, Zhengtang
Abstract : Nanopores on 2D materials have great potential for DNA sequencing, which is attributed to their high sequencing speed and reduced cost. Abstract : Nanopores on 2D materials have great potential for DNA sequencing, which is attributed to their high sequencing speed and reduced cost. However, identifying DNA bases at such a high speed with nanometer precision has remained a big challenge. Here, we implemented theoretical calculations to show the translocation of single-stranded DNA (ssDNA) through solid-state nanopores on a 2D hexagonal boron nitride (h-BN) and graphene sheet. A base-specific ssDNA sequencing technique was devised, based on the individual differences in the ion current responses for the (polyA)16, (polyG)16, (polyC)16, and (polyT)16 bases of ssDNA. Our sequential procedure for sequencing is built on a comparative approach between the current signals obtained from the nanopores to achieve base-specific detection. Our results indicate that at higher voltages (1.0, 1.2, 1.4, 1.6, 1.8 and 2.0 V nm −1 ), DNA translocation is tracked though the 1.5 and 2.0 nm nanopores, and at the 1.5 nm pore size, folded ssDNA close to the nanopore accounts for 93% and 81% of events for graphene and h-BN. Our calculations indicate charge transfer from the graphene to ssDNA, while the reverse happens in the case of the h-BN membrane. These results provide critical insights into our understanding of single molecule sequencing through solid-state nanopore research.